PENGARUH TINGKAT KEPENTINGAN, TINGKAT INFLASI, DAN TINGKAT BAGI HASIL TERHADAP SIMPANAN MUDHARABAH PADA BANK UMUM SYARIAH DAN UNIT USAHA SYARIAH - Rizki Noviansyah; Inten Meutia; Emylia Yuniartie (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2013)
The purpose of this research are to determine the influence of rate of interest, rate of inflation and rate of profit sharing towards mudharabah savings on Bank Umum Syariah and Unit Usaha Syariah in research period from year 2009 until 2012.The number of observations in this study are 58 months, started from January 2009 to October 2012. Techniques of data analysis used in this study are descriptive statistical analysis, the classical assumption test, multiple linear regression analysis and T test.The results of this study indicated that the rate of interest affected significantly and negative on mudharabah savings, rate of inflation affected significantly and negative toward mudharabah savings, while the rate of profit sharing affect positive and significantly to mudharabah savings.